(3GdhGajI GdfhfjIs - (3GdJhfj, GdHTQhj, YHO Gddg Hf eMeO, J (B1071 (3g`s ((3jhSa GdOhHGTjs)
(3ChdgG (B:s
(3hchfg dG ef Yjf GdhVY Yjf GdeYdhe ajMce HGdMbjbI hEdG de jKHJ dcKQI GdMbGFb GdYQajI hGddZhjI(B... (3GdKGdK(B: (3GdCUd aj GddaX Cf jchf eSJYedG ajeG hVY dg(B...s
(3BNQgG (B:s
(3aeG QLY Edi CMO ef GdeQLMGJ GdefUhUI Ch bGe Ydjg Odjd bWYj agh ebHhd hEdG aYOe GdGdJaGJ Edjg CMhW (B... (3hgh MSHj hfYe Gdhcjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI HQbe(B: 83s
(3GdPQjYI HQbe(B: 83s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs